Conspiracy narratives in Roman history - Pagán, Victoria Emma, 1965- (Book collections on Project MUSE., 2004)
"In this first book-length treatment of conspiracy in Roman history, Victoria Pagan examines the narrative strategies that five prominent historians used to disclose events that had been deliberately shrouded in secrecy and silence. She compares how Sallust, Livy, and Tacitus constructed their accounts of the betrayed Catilinarian, Bacchanalian, and Pisonian conspiracies. Her analysis reveals how a historical account of a secret event depends upon the transmittal of sensitive information from a private setting to the public sphere - and why women and slaves often proved to be ideal transmitters of secrets. Pagan then turns to Josephus's and Appian's accounts of the assassinations of Caligula and Julius Caesar to explore how the two historians maintained suspense throughout their narratives, despite readers' prior knowledge of the outcomes. Covering events from 186 B.C.E. to 65 C.E., this book explains the prevalence of conspiracy in the Roman literary imagination and confirms the importance of Josephus and Appian to the development of Roman historical thought."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved